Apparent prevention of neural tube defects by periconceptional vitamin supplementation. Issue 12 (December 1981) - Smithells, R W; Sheppard, S; Schorah, C J; Seller, M J; Nevin, N C; Harris, R; Read, A P; Fielding, D W
Abstract : An earlier preliminary paper is expanded. Women who had given birth to one or more infants with a neural tube defect were recruited into a trial of per conceptional vitamin supplementation. Two hundred mothers attending five centres were fully supplemented (FS), 50 were partially supplemented (PS), and 300 were unsupplemented (US). Neural tube defect recurrences in the study pregnancies were 1 (0.5%), in FS, none in PS, and 13 (4%) in US mothers. The difference in outcome between FS and US mothers is significant. The most likely explanation is that supplementation has prevented some neural tube defects, but further studies are needed.